THU0277 HOW THE AGE AT DIAGNOSIS MODIFIES THE PHENOTYPE OF PRIMARY SJÖGREN SYNDROME: ANALYSIS IN 11, 420 PATIENTS (BIG DATA SJÖGREN PROJECT). (June 2019) - Retamozo, Soledad; Acar-Denizli, Nihan; Ng, Wan Fai; Horváth, Ildiko Fanny; Rasmussen, Astrid; Seror, Raphaèle; Xiaomei, LI; Baldini, Chiara; Gottenberg, Jacques-Eric; Sandhya, Pulukool; Quartuccio, Luca; Priori, Roberta; et al.
Abstract : Objectives: To analyse how the age at diagnosis modifies the phenotype of primary Sjögren syndrome (SS) Methods: The Big Data Sjögren Project was formed in 2014 to take a "high-definition" picture of the main features of primary SS at diagnosis by merging international SS databases. By January 2019, the database included 11, 420 patients from 24 countries of the 5 continents. Results: Women (52.7 vs 54.6 yrs in men, p<0.001) and non-White patients (49.6 vs 53.5 yrs in Whites, p<0.001) were diagnosed at a younger age. Patients without sicca symptoms, with normal oral/ocular diagnostic tests and with positive biopsy were also diagnosed at younger ages (p<0.001 all comparisons). Patients with positive immunological markers had a younger diagnostic age, except for cryoglobulins (p<0.001 all comparisons). Patients without systemic activity (ESSDAI score = 0) were diagnosed at an older age (55.5 vs 52.1 yrs in those with systemic activity, p<0.001). There was a wide variation in the age at diagnosis of patients presenting with systemic activity according to the organ involved. Conclusion: Age at diagnosis plays a key role in the glandular and systemic phenotype expressed by primary SjS patients at the time of diagnosis. Disclosure of Interests: : Soledad Retamozo: None declared, Nihan Acar-Denizli: None declared, Wan Fai Ng: None declared, Ildiko Fanny Horváth: None declared, Astrid Rasmussen: None declared, Raphaèle Seror Grant/research support from: Pfizer, Consultant for: Bristol-Myers Squibb, Pfizer, Amgen, Eli Lilly, Roche, Celgene, GlaxoSmithKline, MedImmune, Xiaomei Li: None declared, Chiara Baldini: None declared, Jacques-Eric Gottenberg Grant/research support from: Bristol-Myers Squibb, Grant/research support from: Bristol-Myers Squibb, Consultant for: Bristol-Myers Squibb, Lilly, Pfizer, Sanofi-Genzyme, UCB Pharma, Consultant for: Bristol-Myers Squibb, Eli Lilly, UCB, Sanofi-Genzyme, Pfizer, Pulukool Sandhya: None declared, Luca Quartuccio: None declared, Roberta Priori: None declared, Gabriela Hernandez-Molina: None declared, Berkan Armagan: None declared, Aike A. Kruize: None declared, Seung-Ki Kwok: None declared, Marika Kvarnstrom: None declared, Sonja Praprotnik: None declared, Damien Sene: None declared, Elena Bartoloni Bocci: None declared, Roser Solans-Laqué: None declared, Maureen Rischmueller Consultant for: Abbvie, Bristol-Meyer-Squibb, Celgene, Glaxo Smith Kline, Hospira, Janssen Cilag, MSD, Novartis, Pfizer, Roche, Sanofi, UCB, Thomas Mandl: None declared, Yasunori Suzuki: None declared, David Isenberg: None declared, Valeria Valim: None declared, Agata Sebastian: None declared, Gunnel Nordmark: None declared, Hendrika Bootsma: None declared, Hideki Nakamura: None declared, Roberto Giacomelli Grant/research support from: Pfizer, Actelion, Speakers bureau: Actelion, Bristol-Myers Squibb, Merck Sharp & Dohme, Abbvie, Pfizer, Sobi, Roche, Valerie Devauchelle-Pensec Grant/research support from: Roche-Chugai, Speakers bureau: MSD, BMS, UCB, Roche, Benedikt Hofauer Consultant for: Consultant for Galvani Bioelectronics for the area of sleep disorders., Michele Bombardieri Grant/research support from: Celgene, Consultant for: Medimmune, Virginia Fernandes Moça Trevisani: None declared, Daniel Hammenfors: None declared, Sandra Pasoto: None declared, Tamer A Gheita: None declared, Fabiola Atzeni: None declared, Jacques Morel: None declared, Cristina Vollenveider: None declared, Sandra Consani-Fernández: None declared, Xavier Mariette Grant/research support from: Servier, Consultant for: AstraZeneca, Bristol-Myers Squibb, GlaxoSmithKline, Janssen, Pfizer, UCB Pharma, Manuel Ramos-Casals: None declared, Pilar Brito-Zerón: None declared